Sustainable Electricity Supply and Poverty Reduction in Nigeria - Eseyin, Oluwasegun; Ogunjobi, Joseph Olufemi (International Journal of Energy Economics and Policy, 2022)
The poverty situation in the rural areas of the country deserves greater attention; the available statistics from the NBS reveal that the majority of the poor are located in the rural areas. It is really impossible to envision industrialization and societal well-being or high standard of living without adequate and reliable electricity supply. Sustainable electricity supply will aid the artisans, traders, farmers with storage facilities, reduce the rural-urban immigration, improve the standard of living in the rural areas, and encourage rural industrialization and capital formation. This study investigates the impact of sustainable electricity supply on poverty reduction in Nigeria. A time series data from 1981 to 2018 was analysed for this study. Based on the outcome of this study, it could be seen clearly that while electricity generation play a significantly role reducing poverty in the country, electricity consumption does not guarantee poverty reduction. Also, apart from the fact that poverty level in the past period is found to have a direct and statistically significant effect on the poverty rate in the current period, it was also revealed that lower unemployment rate does not really translate into reduction in the poverty level in Nigeria. The study therefore recommend that electricity generation should be given more attention and while trying to address the menace of unemployment in the country, underemployment and labour exploitation must also be tackled headlong.